Carbonyl sulfide adsorbent
Patent Information
- Application Number
- JP2025057405
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-29
- Publication Date
- 2026-10-13
AI Technical Summary
【0011】 本発明によれば、硫化カルボニルの除去速度に優れた吸着剤を得ることができる。
Smart Images

Figure 2026165052000001
Abstract
Description
[Technical Field]
[0001] This invention relates to an adsorbent that adsorbs and removes carbonyl sulfide. [Background technology]
[0002] Carbonyl sulfide (COS) is a type of sulfur compound and is known to poison various catalysts. For example, propylene, which has seen increasing demand in recent years, contains trace amounts of carbonyl sulfide, and it is known that if this propylene is sent to the polymerization process without purification, the catalyst for propylene polymerization will be poisoned by the carbonyl sulfide (Patent Document 1).
[0003] As a method for removing such impurities as carbonyl sulfides, distillation, which separates the impurities by utilizing the difference in boiling points, is used industrially. However, carbonyl sulfides contained in propylene are difficult to completely separate by distillation because the boiling points of propylene and carbonyl sulfides are close. Similarly, carbonyl sulfides contained in hydrocarbons with 2 to 6 carbon atoms that have boiling points close to carbonyl sulfides are also difficult to completely separate by distillation (Patent Document 2).
[0004] Thus, as a method for removing carbonyl sulfides, which are difficult to separate by distillation, a method of removing carbonyl sulfides by absorption is known, and adsorbents and absorbent solutions are used as means of absorption.
[0005] For example, Patent Document 3 discloses an absorbent (adsorbent) for sulfur compounds comprising at least one selected from copper carbonate, basic copper carbonate, copper hydroxide, and mixtures thereof. Furthermore, when the sulfur compound is carbonyl sulfide, a method is disclosed in which the carbonyl sulfide is hydrolyzed by γ-alumina used as a support, and the resulting hydrogen sulfide is removed with basic copper carbonate.
[0006] Furthermore, Patent Document 4 discloses an adsorbent for removing carbonyl sulfide containing copper oxide and aluminum compounds. It also discloses a method for accelerating the adsorption rate of carbonyl sulfide by focusing on the solid acidity of aluminum compounds and promoting the hydrolysis activity of carbonyl sulfide. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2012-206944 [Patent Document 2] Japanese Patent Application Publication No. 5-070375 [Patent Document 3] Special Publication No. 9-510141 [Patent Document 4] International release WO2019 / 189550 [Overview of the project] [Problems that the invention aims to solve]
[0008] The present invention aims to provide an adsorbent with excellent carbonyl sulfide removal rate. [Means for solving the problem]
[0009] The inventors of the present invention have found that in a mixture of copper oxide (CuO) and boehmite (AlOOH), focusing on the coordination number of Al, the adsorption and removal rate of carbonyl sulfide is accelerated by controlling the proportion of Al with 5 coordination to a specific range.
[0010] Specifically, in a mixture of copper oxide and boehmite, the Cu content is 30% by mass or more in terms of CuO, the Al content is 10% by mass or more in terms of Al2O3, and it contains a portion of amorphous alumina, that is, 27We found that Al MAS NMR spectra exhibiting peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al, where the ratio of the area of the 5-coordinate Al peak to the sum of the areas of the 4-coordinate, 5-coordinate, and 6-coordinate Al peaks is in the range of 0.5% to 10%, exhibit a fast adsorption and removal rate of carbonyl sulfide. [Effects of the Invention]
[0011] According to the present invention, an adsorbent with excellent carbonyl sulfide removal rate can be obtained. [Modes for carrying out the invention]
[0012] The present invention will be described in detail below. In this specification, the expression "○○~××" means that it is greater than or equal to ○○ and less than or equal to ××, including both a lower limit and an upper limit.
[0013] The present invention is an adsorbent for adsorbing carbonyl sulfides, comprising copper oxide and boehmite, wherein the Cu content is 30% by mass or more in terms of CuO, and the Al content is 10% by mass or more in terms of Al2O3. 27 The carbonyl sulfide adsorbent (hereinafter also referred to as "the adsorbent of the present invention") is characterized by having peaks in the Al MAS NMR spectrum that are attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al, and the ratio of the area of the peak attributed to 5-coordinate Al to the sum of the areas of the peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al is in the range of 0.5% to 10%.
[0014] The adsorbent of the present invention is 27 One characteristic of Al MAS NMR spectra is that they possess peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al, and the ratio of the area of the peak attributed to 5-coordinate Al to the sum of the areas of the peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al is in the range of 0.5% to 10%.
[0015] It is known that the coordination number of Al varies depending on the crystal structure of the Al compound. For example, in γ-alumina, which is often used as a carrier for catalysts and adsorbents, Al exists as 4-coordinate Al and 6-coordinate Al. In addition, in the most chemically stable α-alumina and boehmite (monohydrate of alumina), Al exists as 6-coordinate Al. Furthermore, in amorphous alumina, Al exists as 4-coordinate Al, 5-coordinate Al, and 6-coordinate Al.
[0016] Since the adsorbent of the present invention contains boehmite and 5-coordinate Al, it is considered that boehmite and amorphous alumina coexist in a specific ratio. The presence of Al in the adsorbent in such a state disrupts the symmetry of the crystal structure of boehmite and changes the energy gap, which is considered to make it easier to capture carbonyl sulfide compared to the state of boehmite alone. The ratio of this peak area is preferably in the range of 1% to 1%, more preferably in the range of 1% to 5%. When the ratio of this peak area is within these ranges, the removal rate of carbonyl sulfide tends to increase.
[0017] The adsorbent of the present invention is 27 In the Al MAS NMR spectrum, it has peaks assigned to 4-coordinate, 5-coordinate, and 6-coordinate Al, and the ratio of the peak area assigned to 6-coordinate Al to the total area of the peaks assigned to 4-coordinate, 5-coordinate, and 6-coordinate Al is preferably in the range of 65% to 99%, more preferably in the range of 70% to 95%, and particularly preferably in the range of 70% to 80%. When the ratio of this peak area is within these ranges, the removal rate of carbonyl sulfide tends to be even higher.
[0018] In the adsorbent of the present invention, the proportion of this peak area is thought to represent the proportion of the boehmite crystal structure that remains. By having a large proportion of the peak area attributed to 6-coordinate Al, more of the boehmite crystal structure is retained. On the other hand, by including a small amount of amorphous alumina and controlling the area of the peak attributed to 5-coordinate Al within a certain range, a large portion of the boehmite crystal structure is retained overall, while some of its symmetry is broken, changing the energy gap. This is thought to make it easier to capture carbonyl sulfides compared to the state of boehmite alone.
[0019] The adsorbent of the present invention contains copper oxide. Copper oxide has the function of adsorbing carbonyl sulfide. The reaction in which carbonyl sulfide is adsorbed onto copper oxide is represented by CuO + COS → CuS + CO2. The presence or absence of copper oxide can be determined from the X-ray diffraction pattern. The Cu content in the adsorbent of the present invention is 30% by mass or more in terms of CuO. When this content is high, the amount of carbonyl sulfide adsorbed increases, and when this content is low, the removal rate of carbonyl sulfide is fast, but the amount of carbonyl sulfide adsorbed tends to decrease. Therefore, the Cu content is preferably in the range of 35% by mass to 75% by mass, and more preferably in the range of 40% by mass to 70% by mass, in terms of CuO.
[0020] The adsorbent of the present invention contains boehmite (AlOOH). Boehmite has the function of enhancing the dispersibility of copper oxide as described above. The presence or absence of boehmite can be determined from the X-ray diffraction pattern. The Al content of the adsorbent of the present invention is 10% by mass or more in terms of Al2O3. When this content is higher, the dispersibility of copper oxide as described above tends to be higher. On the other hand, when the Al content is lower, a relatively larger amount of copper oxide can be included, so the amount of carbonyl sulfide adsorbed can be increased. Therefore, the Al content is preferably in the range of 20% by mass to 50% by mass, and more preferably in the range of 30% by mass to 40% by mass.
[0021] The specific surface area of the adsorbent of the present invention is 50 m². 2 / g~300m 2 It is preferable that it be in the range of / g, 75m2 / g to 275m 2 / g is more preferable, and 100m 2 / g to 250m 2 / g is particularly preferable. When this specific surface area increases, the dispersibility of the aforementioned copper oxide tends to be further improved, and the removal rate of carbonyl sulfide also tends to be faster. In addition, when this specific surface area decreases, the physical strength of the adsorbent tends to increase.
[0022] The adsorbent of the present invention may contain components such as a binder, water and a lubricant in addition to the aforementioned boehmite and copper oxide, in a total amount of 20 mass% or less relative to the mass of the adsorbent of the present invention. The binder and water function to increase the physical strength of the adsorbent of the present invention. The lubricant functions to improve the flowability of powder in the production process, and contributes to enhancing productivity.
[0023] The adsorbent of the present invention can be used as an adsorbent for adsorbing and removing carbonyl sulfide. For example, by bringing a fluid containing carbonyl sulfide into contact with the adsorbent of the present invention, carbonyl sulfide is adsorbed onto the adsorbent of the present invention and removed. This fluid may be a gas or a liquid. Since the adsorbent of the present invention is excellent in the removal rate of carbonyl sulfide, carbonyl sulfide can be efficiently removed even in a liquid having lower diffusivity than gas. The adsorbent of the present invention is particularly suitable as an adsorbent for removing carbonyl sulfide contained in a fluid containing an olefin such as propylene.
[0024] The adsorbent of the present invention can be suitably used in a process where the concentration of carbonyl sulfide contained in a fluid is in the range of 0.01 ppm to 30 ppm. In addition, carbonyl sulfide can be efficiently removed in a process where the temperature of the fluid is in the range of -10°C to 70°C.
[0025] The shape of the adsorbent of the present invention may be any conventionally known shape, such as spherical, columnar, or similar shapes. Furthermore, its size (the minimum distance within the adsorbent's dimensions) is preferably in the range of 0.5 mm to 6 mm. Increasing the size of the adsorbent can reduce pressure loss when a fluid containing carbonyl sulfide is passed through it. Decreasing the size of the adsorbent increases the contact efficiency with the adsorbent when a fluid containing carbonyl sulfide is passed through it, thus tending to result in a faster removal rate of carbonyl sulfide.
[0026] The adsorbent of the present invention can be manufactured, for example, by a manufacturing method comprising the following steps (1) to (3). In this manufacturing method, no heat treatment is performed at a temperature exceeding 300°C in the steps after the mixing step. (1) A partial amorphization step in which powdered boehmite is calcined at a temperature of over 300°C but less than 500°C to adjust the ratio of the area of the peak attributed to 5-coordinate Al to the sum of the areas of the peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al to the range of 0.5% to 10. (2) A mixing step in which the boehmite obtained in the partial amorphous step described above is mixed with copper oxide to prepare a mixture. (3) A molding step in which the mixture obtained in the above mixing step is molded to obtain an adsorbent.
[0027] The purpose of the partial amorphous process is to amorphousize a portion of the boehmite to produce five-coordinate Al. In this process, powdered boehmite is calcined at a temperature of over 300°C but less than 500°C to adjust the ratio of the peak area attributed to five-coordinate Al to the sum of the peak areas attributed to four-coordinate, five-coordinate, and six-coordinate Al to a range of 0.5% to 10. In this process, it is preferable to calcine only boehmite. If other components are included in the calcination, the amorphousization of the boehmite may be inhibited or compounds other than amorphous alumina may be formed, making it difficult to produce five-coordinate Al. Furthermore, calcining the boehmite of a molded body makes amorphousization difficult and can easily result in unevenness between the inside and outside of the molded body. Therefore, it is preferable to use powdered boehmite, and it is even more preferable to use powdered boehmite with a particle size of less than 0.5 mm. For example, it is best to use powdered boehmite that has been sieved using a sieve with a mesh size of 0.5 mm or less.
[0028] In the partial amorphous process, it is preferable to calcine the boehmite at a temperature of 350°C to 450°C. If the temperature is too high, amorphous alumina will transition to γ-alumina, making it difficult to retain 5-coordinate Al. Conversely, if the temperature is too low, amorphous alumina will not be formed easily, and 5-coordinate Al will also not be formed easily. In this process, it is sufficient to adjust the ratio of the peak area attributed to 5-coordinate Al to the sum of the peak areas attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al to a range of 0.5% to 10, so the calcination time is not particularly limited. Calcination should be performed for an appropriate time considering conditions such as the amount of boehmite used and the calcination temperature. Furthermore, the calcination of boehmite can be carried out in an atmospheric environment.
[0029] The purpose of the mixing process is to prepare a mixture by mixing the boehmite obtained in the aforementioned partial amorphous process with copper oxide. In this process, these can be mixed using a mixer or other mixing machine. In this process, it is sufficient that the boehmite obtained in the aforementioned partial amorphous process and copper oxide are uniformly mixed. If the mixture is in powder form, it will be generally uniformly mixed if the mixing process is continued for about an hour after the color of the mixture stops changing. If the mixture is in clay form, it will be generally uniformly mixed if the mixing process is continued for about an hour after the power fluctuations of the mixer become small.
[0030] The copper oxide used in the mixing process may be obtained by calcining a copper compound or by synthesizing it in an aqueous solution. When calcining a copper compound, it can be obtained by calcining copper compounds such as copper acetate, basic copper carbonate, and copper nitrate at 300°C to 500°C. When synthesizing copper oxide in an aqueous solution, it can be obtained by heating an aqueous solution containing dispersed copper hydroxide to 50°C or higher.
[0031] In the mixing step, the state of the mixture can be adjusted to match the molding method used in the molding step described later. For example, if extrusion molding is used in the molding step described later, the mixture should be made clay-like. At this time, since mixing only the boehmite and copper oxide obtained in the partial amorphous step described above does not easily result in a clay-like consistency, it is preferable to add a binder and water as appropriate. As the binder, an inorganic binder may be used, an organic binder may be used, or both may be used in combination. As the inorganic binder, a sol containing fine particles such as silica and alumina can be used, and it is preferable to use a sol containing fine silica particles. As the organic binder, it is preferable to use a polymer-based organic binder, for example, polyvinyl alcohol, wheat starch, methylcellulose, etc. In particular, carboxymethylcellulose ([C6H7O2(OH)3] n) and the like are preferred. This contains three hydroxyl groups per glucose, but the hydrogen atoms of the hydroxyl groups may be substituted with other functional groups R. For example, R may be a methoxy group (-OCH3) or a hydroxypropoxy group (-OC3H6OH). Note that the organic binder does not contain organic materials consisting only of carbon, such as graphite, or organic materials whose main component is carbon, such as activated carbon. For example, when tableting is used in the molding process described later, the mixture is made into a powder. At this time, if the fluidity of the powder is low and productivity is poor, it is good to use a lubricant such as graphite to improve the fluidity.
[0032] The purpose of the molding process is to obtain an adsorbent by molding the mixture obtained in the aforementioned mixing process. For example, the mixture can be molded by methods such as extrusion molding or tablet molding. The adsorbent obtained in this process can be dried at a temperature of 300°C or lower if necessary. In particular, if there is wetness on the surface of the adsorbent, drying removes the moisture on the surface of the adsorbent, preventing the adsorbents from solidifying together. Furthermore, the amount of moisture contained in the adsorbent can be adjusted to a desired range.
[0033] In the above manufacturing method of the present invention, heat treatment at temperatures exceeding 300°C is not performed in the series of steps from the mixing step to the molding step. If heat treatment is performed at temperatures exceeding 300°C, the coordination number of Al may change due to the transformation of amorphous alumina to γ-alumina or reaction with components other than boehmite. [Examples]
[0034] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples.
[0035] The following raw materials were used in the examples and comparative examples. [Raw materials used] Boehmite powder 1: Manufactured by SASOL, product name: PURAL SCF-70 Boehmite powder 2: Manufactured by Kawai Lime Industry Co., Ltd., Product name: Cerasure BMB-07 Inorganic binder: Silica sol (SiO2 content: 5% by mass) Organic binder: Shin-Etsu Chemical Co., Ltd., Metroze 90SH Copper oxide powder: Powdered copper oxide obtained by the following preparation method.
[0036] [Preparation of copper oxide] A mother liquor was prepared by dissolving 231 g of sodium hydroxide in 5.8 kg of deionized water. Next, an additive solution was prepared by dissolving 676 g of copper sulfate pentahydrate in 2.6 kg of deionized water. The mother liquor and the additive solution were mixed while both were heated to generate a copper oxide precipitate. The slurry containing the copper oxide precipitate was filtered to separate the precipitate, and then thoroughly washed to obtain a copper oxide precipitate cake. This precipitate cake was dispersed in 4.0 kg of deionized water to obtain a copper oxide slurry. The copper oxide slurry was dried to obtain powdered copper oxide.
[0037] The following measurements were performed on the raw materials and products.
[0038] [1] X-ray diffraction measurement X-ray diffraction measurements were performed using a Rigaku MultiFlex X-ray diffractometer. First, the sample was ground in a mortar and pestle and packed onto a sample plate so that the surface of the sample was flat. Next, this sample plate was set in the X-ray diffractometer, and X-ray diffraction measurements were performed under the following conditions: Cu-Kα radiation source, tube voltage 40kV, tube current 20mA, scanning range 10-70°, divergence slit 1.0mm, scattering slit 1.0mm, light-receiving slit 0.3mm, and scan speed 4° / min. If even one peak attributed to boehmite was confirmed in the obtained X-ray diffraction pattern, it was considered to contain boehmite. Also, if even one peak attributed to copper oxide was confirmed, it was considered to contain copper oxide.
[0039] [2] 27 Al MAS NMR measurement Agilent 27NMR spectra were measured using an Al MAS NMR spectrometer (VNMRS-600, 1H resonance frequency: 600 MHz). First, the sample was calcined at 300°C for 1 hour. Next, the calcined sample was exposed to an atmosphere of 60% relative humidity and conditioned for 24 hours. The conditioned sample was then uniformly packed into a 3.2 mm diameter sample tube. 27 The sample tube was placed in the Al MAS NMR spectrometer. At this time, the sample tube was rotated at a speed such that the magic angle (54.7°) relative to the external magnetic field was 20 kHz. 27 The Al resonance frequency was 156.3 MHz. 27 For the Al-NMR chemical shift criterion, the peak of a 1 mol / l Al(NO3)3 aqueous solution was set to 0 ppm, and the number of FID integrations was set to 256. The single-pulse method was used for measurement, with a pulse flip angle of 10° and a pulse repetition time of 0.1 s. Using the included analysis software, the obtained spectra were approximated using the Voigt function with Origin to perform waveform separation and background removal, and the presence or absence of peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al was confirmed. At this time, the peak appearing around 67 ppm was identified as 4-coordinate Al, the peak appearing around 36 ppm as 5-coordinate Al, and the peak appearing around 9 ppm as 6-coordinate Al. From the area of each peak, the ratio of the area of the peak assigned to 5-coordinate Al to the sum of the areas of the peaks assigned to 4-coordinate, 5-coordinate, and 6-coordinate Al was calculated.
[0040] [3] ICP emission spectroscopy The sample was dissolved in acid, and the filtrate was diluted with water to an appropriate concentration. Then, the Cu content (in CuO equivalent) and Al content (in Al2O3 equivalent) were measured using an ICP emission spectrometer (Agilent 730ICP-OES, inductively coupled plasma emission spectrometry). Using these Cu and Al content values, the Cu and Al content (in CuO equivalent and Al2O3 equivalent) contained in the adsorbent were calculated, respectively, based on the total amount of the adsorbent.
[0041] [4] Specific surface area measurement The specific surface area of a sample was measured using the BET single-point method with a specific surface area analyzer (Macsorb1220) manufactured by Mountec. First, approximately 0.1 g of the sample was placed in the analyzer and set in the analyzer. Next, nitrogen gas was circulated through the analyzer and degassed at 250°C for 40 minutes. Furthermore, a mixed gas of 30% by volume of nitrogen and 70% by volume of helium was circulated through the analyzer after degassing and maintained at liquid nitrogen temperature to allow nitrogen to be adsorbed to equilibrium on the sample. Subsequently, the temperature of the analyzer was gradually increased to room temperature while the mixed gas was circulated, and the amount of nitrogen desorbed during this time was measured. The surface area of the sample was calculated from the amount of desorbed nitrogen, and the specific surface area per gram of sample was calculated by dividing this by the mass of adsorbent after measurement.
[0042] [5] Carbonyl sulfide adsorption test The adsorption rate of carbonyl sulfide from the sample was evaluated. First, a 1-hexene solution (Feed) with a COS concentration of 10 ppm was prepared. Next, the adsorbent was packed into a reaction tube to a layer height of 8 cm, and this reaction tube was attached to a COS adsorption test apparatus. Then, the reaction tube was heat-treated at 170°C for 1 hour with nitrogen flowing through it, and then cooled to room temperature. After cooling to room temperature, the Feed was flowed into the reaction tube at a supply rate of 3.2 g / min. The liquid at the inlet and outlet of the reaction tube was sampled at predetermined intervals, and the COS concentration was analyzed using a gas chromatograph equipped with an SCD detector (Agilent Technologies, model 7890B). The rate constant was calculated from the difference between the inlet COS concentration and the outlet COS concentration when the cumulative sulfur adsorption amount was 0.2%, and this was taken as the COS removal rate.
[0043] [Example 1] Boehmite powder 1 was calcined at 350°C for 2 hours to obtain a powder. This powder was used as a measurement sample, and the aforementioned {1}{2} measurements were performed, revealing that it contained boehmite. 27In the Al MAS NMR spectrum, peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al were observed, and it was confirmed that the ratio of the area of the peak attributed to 5-coordinate Al to the sum of the areas of the peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al was 1.1%. 85.6 g of this powder, 96 g of copper oxide powder, 48.0 g of inorganic binder, 3.8 g of organic binder, and 80.0 g of deionized water were placed in a mixer and uniformly mixed to obtain a clay-like mixture. This clay-like mixture was put into an extruder and extruded to form a cylindrical shape with a diameter of 1.8 mmφ and a length of 3-5 mm to obtain a molded body. This molded body was dried at 120°C for 16 hours to obtain an adsorbent. The obtained adsorbent was used as a measurement sample, as described above. Measurements [3] to [5] were performed. The results are shown in Table 1.
[0044] [Example 2] The adsorbent was obtained in the same manner as in Example 1, except that boehmite powder 1 was calcined at 400°C for 2 hours to obtain the powder. Measurements were also performed in the same manner as in Example 1. The results are shown in Table 1.
[0045] [Example 3] An adsorbent was obtained in the same manner as in Example 1, except that boehmite powder 1 was calcined at 450°C for 2 hours to obtain the powder. Measurements were also performed in the same manner as in Example 1. The results are shown in Table 1. Comparative Example
[0046] [Comparative Example 1] The adsorbent was obtained using the same method as in Example 1, except that the boehmite powder 1 was not calcined. Measurements were also performed in the same manner as in Example 1. The results are shown in Table 1.
[0047] [Comparative Example 2] The adsorbent was obtained using the same method as in Comparative Example 1, except that boehmite powder 2 was used instead of boehmite powder 1. The same measurements as in Comparative Example 1 were also performed. The results are shown in Table 1.
[0048] [Table 1]
Claims
[Claim 1] An adsorbent that adsorbs carbonyl sulfide, It contains copper oxide and boehmite, with a Cu content of 30% by mass or more in terms of CuO, and an Al content of Al 2 O 3 This is equivalent to 10% by mass or more. 27 An adsorbent characterized by having peaks in the Al MAS NMR spectrum that are attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al, and the ratio of the area of the peak attributed to 5-coordinate Al to the sum of the areas of the peaks attributed to 4-coordinate, 5-coordinate, and 6-coordinate Al is in the range of 0.5% to 10%.
Citation Information
Patent Citations
Method for simultaneously removing carbonyl sulfide and carbon monoxide contained in propylene
JP1993070375A
absorbent
JP1997510141A
Method for removing carbon monoxide (CO) and / or carbonyl sulfide (COS) contained in propylene
JP2012206944A
adsorbent
WO2019189550A1